The admissibility and limits of Member States’ intervention in the free determination of the prices of agri-cultural products. Legal doctrinal considerations in the light of the case law of the Court of Justice of the European Union - Busse, Christian (Przegląd Prawa Rolnego, 2021)
The aim of this article was to answer the question to what extent the Member States may, by adopting national regulations, interfere in the free determination of the prices of agricultural products. Price regulation instruments are an integral part of the Common Agricultural Policy. According to the traditional view, EU secondary legislation on the agricultural market contains an implicit prohibition on national price regulation. Moreover, an alternative justification for such a prohibition may also be derived directly from the TFEU. The article assesses the admissibility of the application of minimum prices for agricultural products and foodstuffs depending on production costs, discussing various aspects.